Application of Multi-Omics Technologies to the Study of Phytochromes in Plants - Shumei Wu; Yue Gao; Qi Zhang; Fen Liu; Weiming Hu (MDPI AG, 2024)
Phytochromes (phy) are distributed in various plant organs, and their physiological effects influence plant germination, flowering, fruiting, and senescence, as well as regulate morphogenesis throughout the plant life cycle. Reactive oxygen species (ROS) are a key regulatory factor in plant systemic responses to environmental stimuli, with an attractive regulatory relationship with phytochromes. With the development of high-throughput sequencing technology, omics techniques have become powerful tools, and researchers have used omics techniques to facilitate the big data revolution. For an in-depth analysis of phytochrome-mediated signaling pathways, integrated multi-omics (transcriptomics, proteomics, and metabolomics) approaches may provide the answer from a global perspective. This article comprehensively elaborates on applying multi-omics techniques in studying phytochromes. We describe the current research status and future directions on transcriptome-, proteome-, and metabolome-related network components mediated by phytochromes when cells are subjected to various stimulation. We emphasize the importance of multi-omics technologies in exploring the effects of phytochromes on cells and their molecular mechanisms. Additionally, we provide methods and ideas for future crop improvement.